Cultural Foundations of Parental Educational Motivation in Indigenous Communities - Mundiri, Akmal; Fatimah, Siti (Journal of Educational Management Research, 2024)
This study aims to understand the motivation behind parental education in the Tengger Tribe Indigenous Community, located in Sukapura, Probolinggo. The Tengger Community faces a challenge in maintaining its traditional culture while providing children with opportunities to access increasingly formal education, which is essential in the modern world. In this context, parents in the community strive to preserve their values, customs, and religion, to provide education that can improve the quality of life for socioeconomically disadvantaged children. Approach: This study employs a qualitative design, utilizing case studies that involve in-depth interviews and observations to gain a deeper understanding of the dynamics of parental motivation. Research results indicate that the child’s participation influences parental motivation for education in the Community ethnic group, which involves balancing the preservation of culture and tradition with the demands of globalization and technological progress, in order to enhance welfare and the economy, while also striving to maintain community harmony.